Evolving culturally competent veterinary care: a community-based partnership with the Santee Nation - Orchard, Ronald J.; LaPointe, Deon; Miner, Sara; Conrad, Cayley; Blevins, Chris; Jeje, Emmanuel (Frontiers in Veterinary Science, 2026)
Access to veterinary care remains a profound equity issue across the United States, particularly in Indigenous communities where animals hold vital cultural and spiritual significance. This case study examines a longitudinal, community-based partnership between Kansas State University’s College of Veterinary Medicine and the Santee Nation, offering a model of culturally competent veterinary outreach grounded in the principles of One Health, cultural humility, and decolonizing education. Over 7 years, the program has evolved from a small animal service-learning initiative into a multifaceted, community-guided collaboration that integrates student learning, tribal leadership, and interprofessional engagement. Key programmatic components include structured cultural preparation, provision of mobile veterinary care—including equine services prioritized by the community—relationship-centered practices, and ongoing feedback loops. Students engage in implicit bias assessments, autoethnographic reflection, and historical learning about land-grant institutions and tribal sovereignty. Clinical interactions emphasize relational accountability, transparency, and the centering of Indigenous knowledge. Community members, in turn, act as co-educators and co-designers, reshaping what competent veterinary care looks like within a tribal context. Findings illustrate how veterinary outreach, when framed through reciprocal partnership rather than charity, can build trust, improve access, and foster professional identity formation rooted in equity. This model aligns with national calls for culturally responsive care and offers a replicable framework for institutions seeking to reimagine their role in tribal health and veterinary education. The program advances the scholarship of engagement by demonstrating how veterinary institutions can co-create just and sustainable systems of care alongside historically excluded communities.